2021
DOI: 10.1038/s41536-021-00191-7
|View full text |Cite
|
Sign up to set email alerts
|

Current progress of rehabilitative strategies in stem cell therapy for spinal cord injury: a review

Abstract: Stem cell-based regenerative therapy has opened an avenue for functional recovery of patients with spinal cord injury (SCI). Regenerative rehabilitation is attracting wide attention owing to its synergistic effects, feasibility, non-invasiveness, and diverse and systemic properties. In this review article, we summarize the features of rehabilitation, describe the mechanism of combinatorial treatment, and discuss regenerative rehabilitation in the context of SCI. Although conventional rehabilitative methods hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 104 publications
0
29
0
Order By: Relevance
“… 166 Thus, stem cell-based transplantation, including olfactory ensheathing cells (OECs), MSCs, and NSPCs, has opened an avenue for functional recovery of SCI, which has been enhanced by exercise training as well. 167 It has been reported that exercise enhances the effect of OEC grafts in super acute thoracic cord transected rats, inducing a fourfold increase in regenerating axons within the caudal stump of the transected spinal cord. 168 Additionally, exercise significantly promoted NSPCs graft survival and differentiation more into neurons and oligodendrocytes, enhancing myelination, and restoration of serotonergic fiber innervation in the lumbar spinal cord via reducing stress caused by active oxygen or active nitrogen through insulin-like growth factor 1 (IGF-1) signaling, which provided more theoretical basis for exercise rehabilitation and pharmacological mimetics 169 (Fig.…”
Section: Benefits Of Exercise On Tissue Regenerationmentioning
confidence: 99%
“… 166 Thus, stem cell-based transplantation, including olfactory ensheathing cells (OECs), MSCs, and NSPCs, has opened an avenue for functional recovery of SCI, which has been enhanced by exercise training as well. 167 It has been reported that exercise enhances the effect of OEC grafts in super acute thoracic cord transected rats, inducing a fourfold increase in regenerating axons within the caudal stump of the transected spinal cord. 168 Additionally, exercise significantly promoted NSPCs graft survival and differentiation more into neurons and oligodendrocytes, enhancing myelination, and restoration of serotonergic fiber innervation in the lumbar spinal cord via reducing stress caused by active oxygen or active nitrogen through insulin-like growth factor 1 (IGF-1) signaling, which provided more theoretical basis for exercise rehabilitation and pharmacological mimetics 169 (Fig.…”
Section: Benefits Of Exercise On Tissue Regenerationmentioning
confidence: 99%
“…Rand and Ambrosio recently defined regenerative rehabilitation as “The application of rehabilitation protocols and principles together with regenerative medicine therapeutics toward the goal of optimizing functional recovery through tissue regeneration, remodeling, or repair.” Regenerative rehabilitation studies seek to investigate modifications of complex cell–cell and cell–matrix interactions induced by in vivo physical stimuli to achieve optimal functional outcomes secondary to regenerative treatments [ 26 ]. Tashiro et al categorized regenerative rehabilitation for SCI as conditioning/reconditioning, functional training, and physical exercise, according to the molecular and behavioral mechanisms [ 41 ]. To our knowledge, no study has investigated the safety of regenerative rehabilitation, but no adverse effects have been observed to date.…”
Section: Regenerative Rehabilitationmentioning
confidence: 99%
“…Consequently, some clinical trials of stem cell treatment excluded patients who showed a possibility of recovery with rehabilitation [ 39 ] or did not receive any rehabilitative training [ 40 ]. A recent review reported that 18 out of 22 clinical studies of acute-to-subacute SCI and 17 out of 31 studies of chronic SCI published up to the middle of 2021 did not provide any details about rehabilitation protocols [ 41 ]. To develop regenerative rehabilitation and optimize rehabilitation, we should accurately elucidate the mechanisms of rehabilitation and assess whether recovery can be induced by combinatorial treatment with transplantation and rehabilitation, or by single treatments.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was not describing about the timing of rehabilitation and what type of rehabilitation was performed (Huang et al, 2012). To our knowledge, unfortunately, this is the only study investigating the relationship between functional recoveries and the sufficient/insufficient of neurorehabilitation following stem cell treatment in chronic SCI patients (Tashiro et al, 2021). There were several combinatory treatment of stem cell therapy (Umbilical cord blood cell and BMSC) and neurorehabilitation in ongoing clinical trials (NCT03979742, NCT01354483, and NCT01393977, see footnote 1).…”
Section: Neurorehabilitation In Experimental and Clinical Studies Fol...mentioning
confidence: 99%